2008
DOI: 10.3844/ajbbsp.2008.336.344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stages of Maturity and Ripening Conditions on the Biochemical Characteristics of Tomato

Abstract: An experiment was carried out to evaluate the biochemical characteristics of tomato in different maturity stages and ripening conditions. Tomato (Lycopersicon esculentum Mill) fruits (cv. Ruma VF) were harvested at the three maturity stages viz., mature green, half ripen and full ripen and stored at three condition control (without covering), straw covering and CaC 2 + straw covering. At that time ascorbic acid, pH, titrable acidity, sugar (reducing, non-reducing sugar and total) percentage, TSS and TSS and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 7 publications
13
48
0
Order By: Relevance
“…The maximum content of ascorbic acid appears in half-ripe tomatoes (the pink stage), after which it declines (Moniruzzaman et al, 2008). Dhall and Singh (2013) report that ethephon caused an increase in the content of ascorbic acid and in titrimetric acidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum content of ascorbic acid appears in half-ripe tomatoes (the pink stage), after which it declines (Moniruzzaman et al, 2008). Dhall and Singh (2013) report that ethephon caused an increase in the content of ascorbic acid and in titrimetric acidity.…”
Section: Discussionmentioning
confidence: 99%
“…is considered as an indicator of good tomato quality (Moniruzzaman et al, 2008). During ripening the ratio of extract to organic acids increases; in fully ripe tomatoes it is about 16 and strongly influences acceptance of flavour (Malundo et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Zapata, Gerard, Davies, & Schvab (2007) reported that the synthesis of vitamin C in tomatoes were higher in those grown in the months of highest average temperature. Moneruzzaman, Hossain, Sani, and Saifuddin (2008) reported that the ascorbic acid decreased with the ripening of tomato fruits; also during the storage at 30 ± 1 °C the ascorbic acid decreased in 20% after 6 days of storage. It is known that ascorbic acid decreases with increase in temperature (Emese & Nagymate, 2008); however, Oyetade, Oyeleke, Adegoke, and Akintunde (2012) performed an experiment of the stability of ascorbic acid from different sources (laboratory grade, pharmaceutical tablets, and grape juice) storage at different temperature (4-5 °C, room temperature, and 35 °C).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in agreement with the Basak et al (1998) who reported that auxin and gibberellins could significantly increase the total soluble solids contents of the fruit in sweet cherry. The TSS content of tomato fruits increased with gradual advancement of fruit maturity and the highest TSS was recorded in fully ripened tomatoes (Moneruzzaman et al 2008). The present results for the correlation of the peel color with TSS were in agreement with Moneruzzaman et al (2009).…”
Section: Discussionmentioning
confidence: 99%